Ecological, social and economic impacts of trypanotolerance: collaborative research in Central and West Africa - Reid, Robin S.; Curry, J.J.; Swallow, B.M.; Mukhebi, A.W.; Perry, Brian D.; Ellis, J.E. (International Laboratory for Research on Animal Diseases, 1994)
The controversy over the possible impacts of trypanosomiasis control on African ecological and socioeconomic systems exemplifies the classic polarization of arguments for development and conservation. On one hand, Africa's rapidly expanding human populations require expanded food supplies, and trypanosomiasis is a major constraint to livestock and crop production in the areas that have the greatest potential to expand food production on the continent. On the other hand, researchers suggest that trypanosomiasis control and subsequent agricultural expansion may result in a sequence of environmental changes. ILRAD, ILCA and Winrock International are launching a project with regional and national partners to evaluate the impacts of trypanosomiasis control at the continental, national and local levels. Trypanotolerant livestock will feature predominantly in the analyses for West and Central Africa. This paper presents the conceptual framework and methods that will be used in the project. The proposed study objectives, hypotheses, methods and expected outputs of the research are also discussed.